Investigation of temperature effects of a low-level laser source within the muscle phantom - Neslişah Gün; Baki Karaböce; MirHasan Yu. Seyidov; Hüseyin Okan Durmuş (International Journal of Advances in Applied Sciences, 2021)
In this study, temperature effects of a low-level laser source were investigated in a muscle phantom within 20, 40, 60, and 80 seconds time intervals. A temperature meter device having a 5-channel and 10 kΩ negative temperature coefficient (NTC) type thermistor sensors were developed in TÜBİTAK UME Medical Metrology Laboratory for these special temperature measurements. The muscle phantom poured into a phantom container that was specially designed for 5-channel sensor placement and printed in a 3D printer. It has also been acoustically confirmed that the phantom has muscle phantom characteristics. As a result of this study, it is concluded that the laser source used is safe and suitable at therapy usage within the specified times in terms of the detected temperatures.